Morphological Characteristics of Mangroves in Saltwater Lakes under Hypersaline Conditions in Gili Meno North Lombok, Indonesia - Jannathin Salsabila; Edi Muhamad Jayadi; Firman Ali Rahman (Jurnal Inovasi Pendidikan dan Sains)
Mangrove ecosystem is an environment formed from the interaction between land and sea waters, playing an important role as a natural protector of the coast from abrasion, tsunamis, and supporting biodiversity. This study aims to identify the types of mangroves in the Gili Meno Salt Lake Mangrove Ecotourism area, Gili Indah Village, Pemenang District, North Lombok Regency. This area has an extreme salinity level, reaching 54.00 ± 0.82 ppt, far above the average for Indonesian sea waters (33–43 ppt). The research method is qualitative through direct observation and leaf organ sampling. The identification results found five tree-type mangrove species with different root systems: respiratory roots (Avicennia marina, Excoecaria agallocha), supporting roots (Rhizophora apiculata), knee roots (Bruguiera cylindrica), and pencil roots (Lumnitzera racemosa). The five species have alternating single leaves, but show differences in leaf morphology, such as shape, size, color, and leaf position. These morphological variations are influenced by differences in habitat, environmental parameters, and nutrient sources, including substrate conditions, salinity, and temperature, which play an important role in the morphological structure of mangroves